ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI SALAK PONDOH DI DESA TIGA JUHAR KECAMATAN STM HULU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Tharmizi Hakim (Universitas Pembangunan Panca Budi, 2018)
This study was intended to analyze and see factors that influence the production of salak pondoh in Tiga Juhar Village, with various production theories and using several variables as a measurement tool in this study consisted of land area, labor, fertilizer, seeds and capital. The data used in this study were primary data that was obtained by distributing a list of questions that have been prepared by interviewing farmers directly. Sampling criteria with judgment sampling method (purposive sampling) is the technique of determining the sample of research on several characteristics of the members adjusted to the purpose of the researcher. The researcher choosen the sample to fulfill the goal by ensuring that all the pepulations had certain characteristics, with the consideration that some research samples were homogeneous or on average have a land area. The samples in this study were 70 farmers from the total number of salak pondoh farmers (243 people) in Tiga Juhar village. Data analysis method used in this study, was multiple linear regression analysis method, this method was used to predict the influence of a dependent variable based on independent variables using the SPSS 2017 software application tool. The results showed that (1) the estimated estimated salak pondoh production model gave positive results because all the observed independent variables showed that the variables of Land Area, Labor, Fertilizer, Seedlings and Capital had a significant effect on the production of salak pondoh in Tiga Juhar Village. (2) Analysis of estimation data showed a significant influence of dependent variables with independent variables. This can be seen from the R-Squared test of 0.963 which means that free variation (land area, labor, fertilizer, seeds and capital) had significant effect on salak production by 96 percent and the remaining 4 percent by other variables not found in the estimation model. While the F test was 331,529 or the probability value of 0.0000 had a significant effect on the production of salak pondoh at a 95% confidence level.